1998
DOI: 10.1159/000015168
|View full text |Cite
|
Sign up to set email alerts
|

Centrosome amplification as a possible mechanism for numerical chromosome aberrations in cerebral primitive neuroectodermal tumors with TP53 mutations

Abstract: Although alterations in chromosome number have frequently been detected in human tumor cells and associated with tumor initiation and progression, the causal mechanisms are still not understood. One protein known to be involved in maintaining genetic stability is tumor suppressor p53. In mice, p53 has been implicated in the maintenance of diploidy (Cross et al., 1995) and the regulation of centrosome duplication (Fukasawa et al., 1996). Here we report on cerebral primitive neuroectodermal tumors that lacked th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
61
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(67 citation statements)
references
References 15 publications
6
61
0
Order By: Relevance
“…Since p53 is important for centrosome duplication, the conclusion of this observation is that centrosome amplification can occur in tumours lacking wild type p53 and could be a mechanism for the generation of numerical chromosomal aberrations [54].…”
Section: Neuroectodermal Tumoursmentioning
confidence: 91%
See 1 more Smart Citation
“…Since p53 is important for centrosome duplication, the conclusion of this observation is that centrosome amplification can occur in tumours lacking wild type p53 and could be a mechanism for the generation of numerical chromosomal aberrations [54].…”
Section: Neuroectodermal Tumoursmentioning
confidence: 91%
“…Breast and prostate cancer [45][46][47] Bladder cancer and Malignant biliary tract disease [48,49] Pancreatic cancer [50] Head and neck sguamous cell carcinoma Oral squamous carcinomas [51][52][53] Neuroectodermals tumours [54] these were found centrosome hyperamplification. Since the percentage is so high, it is implied that this could be used as a marker for HNSCC [51].…”
Section: Abnormalities In Centrosomes In Various Cancersmentioning
confidence: 99%
“…Abrogation of the regulatory mechanism that ensures the coordinated progression of centrosome duplication with other cell cycle events, and that limits centrosome duplication to only once per cell cycle, leads to centrosome hyperampliÂźcation as depicted in p537/7 cells (reviewed in Winey, 1996;Brinkley and Goepfert;1998). The strong correlation between p53 inactivation and the occurrence of centrosome hyperampliÂźcation has also been reported in various types of human cancers (Weber et al, 1998;Carroll et al, 1999). We have recently shown that p53 is involved in the regulation of centrosome duplication directly, and not through inducing other mutations, since reintroduction of wild-type p53 into p537/7 cells restores the normal centrosome duplication cycles (Tarapore et al, 2001).…”
Section: Introductionmentioning
confidence: 97%
“…13,15,[20][21][22][24][25][26] Hematological malignancies including acute and chronic myeloid leukemias, multiple myelomas and both Hodgkin-and nonHodgkin lymphomas also display centrosome aberrations at high frequencies. 16,17,[27][28][29][30][31]46 Moreover, centrosome aberrations have been shown to occur already in many premalignant lesions, including preinvasive cancers of prostate, uterine cervix, breast and pancreas as well as in myelodysplastic syndromes and monoclonal gammopathies of undetermined significance.…”
Section: Discussionmentioning
confidence: 99%
“…Centrosome aberrations have recently been described in both solid tumors and hematological malignancies. [13][14][15][16][17][18][19][20][21][22][23][24] Moreover, it could also be demonstrated that centrosome aberrations correlate with karyotype abnormalities in solid neoplasias of different origin, 13,15,[20][21][22][24][25][26] as well as in acute and chronic myeloid leukemias, myelodysplastic syndromes, multiple myelomas and nonHodgkin's lymphomas. 16,17,[27][28][29][30][31] The extent of centrosome aberrations was higher in aggressive and rapidly proliferating nonHodgkin's lymphomas as compared to indolent lymphomas.…”
mentioning
confidence: 99%